Simulation of Long-Term Changes of the Equilibrium Line Altitude in the Central Chilean Andes Mountains Derived From Atmospheric Variables During the 1958–2018 Period - Barria, Ignacio; Carrasco, Jorge; Casassa, Gino; Barria, Pilar (Frontiers in Environmental Science, 2019)
Annual variability and trends of the Equilibrium Line Altitude (ELA) in the Andes mountains can be studied using the annual average of the 0°C isotherm altitude (ZIA) and the annual precipitation accumulation in mountains areas. Carrasco et al. (2005, 2008) obtained the ELA along the western side of the Andes from about 18°S to 55°S, using the radiosonde data from the Chilean areological stations located at Antofagasta (23°26° S, 70°26°W; northern region), Quintero/Santo Domingo (32°47°S, 71°33°W / 33°38°S, 71°18°W; central region), Puerto Montt (41°26°S, 73°07°W, southern region) and Punta Arenas (53°00°S, 70°07°W; austral region). These data along with the annual precipitation in the mountains allowed inferring the ELA behaviour at the corresponding latitudinal location for the 1958-2006 period. Here, the study is restricted to the central Chilean Andes between 30º and 38ºS and update the analysis until 2017. Results revealed an overall increase in elevation of the ELA of ~115.1 m (p<0.1), during the 1958-2017 period, but most of the increment occurred after the 1976/77 climate shift. A significant increase of ~369.6 m (p<0.05) took place between 2000 and 2017, mainly due to the megadrought that has been affecting the central and southern Chile since 2010.